Human Assets and Management Dilemmas: Coping With Hazards On the Road to Resource-Based Theory - Coff, Russell (Academy of Management Review, 1997)
Resource-based theorists argue that human assets can be a source of sustainable advantage because tacit knowledge and social complexity are hard to imitate. However, these desirable attributes cause dilemmas that may prevent firms from generating an advantage. This article develops a framework for analyzing and coping with these challenges. Although the problem arises from the strategy literature, the solutions are drawn from the organizational behavior, human resource management, human capital, and professions literatures. Finally, I examine implications for how insights from these diverse literatures can be integrated to guide future strategy research.